Devising quality control criteria for manufacturing control valves of the type «nozzle-flap» - Lytviak, Oleksandr; Komar , Sergii; Derevyanko , Oleksandr; Durieiev , Viacheslav (Eastern-European Journal of Enterprise Technologies, 2021)
This paper is a continuation of research into the causes and ways to eliminate the generation of self-oscillations in the system of automatic regulation of rotations of the free turbine in the turboshaft gas turbine engines of helicopters. The study of dynamic processes in the system of automatic regulation of free turbine’s rotations in a turboshaft GTE has shown that one of the reasons for the development of self-oscillations is the poor performance of the control valve of the type «nozzle-flap» in the rotation regulator’s hydraulic drive. At a pump-regulator plant, the criterion for the quality of control valve execution or repair implies that the geometric size of the valve parts and the flow rate of working fluid through the valve when the flap is closed meet the technical requirements. As practice shows, this is not enough. With this approach, valve defects manifest themselves only during the tests of assemblies as part of the engine. This paper proposes a method to examine the characteristics of control valves such as «nozzle-flap», as well as criteria for assessing the quality of their execution. Experimental characteristics of control valves such as «nozzle-flap» for an actual regulator of free turbine rotation frequency are given. New data on the outflow of liquid from the nozzle with a flap have been obtained. It is shown that the destruction of the stagnation zone in the nozzle tip could result in that the valve flow rate increases, which negatively affects the characteristics of the hydraulic drive and regulator in general. A technique has been proposed to improve the stability of the valve’s performance by increasing the relative length of the nozzle. It is shown that the most informative characteristic of the valve is the dependence of flow rate on the position of the flap. Based on this characteristic, it is possible to determine the criteria for rejecting valves without testing them as part of the assembly